Analysis of the Effects of Economic Growth, Investment, Education, and Technology on Open Unemployment Rate in Java - Salsabhila, Atira; Sakti, Rachmad Kresna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The open unemployment rate in Java Island remains relatively high compared to other islands in Indonesia, even exceeding the national average. Therefore, appropriate solutions are needed to address this unemploymet issue. This study aims to determine and analyze the influence of economic growth, investment, education, and technology on the open unemployment rate in the 6 provinces of Java Island during the 2015-2023 period. This research is a quantitative study using panel data regression analysis. The data used are secondary data obtained from BPS. The result of this study show that economic growth has a negative and significant effect on the open unemployment rate, education has a positive and significant effect on the open unemployment rate, while investment and technology have no effect on the open unemployment rate.